Geotouristic bicycle path around Nowy Targ (Carpathians, Poland) - Szczęch, Mateusz; Cieszkowski, Marek; Szczęch, Szymon; Chodyń, Rafał (Geotourism/Geoturystyka, 2023)
The area in the vicinity of Nowy Targ is located within the northern part of the Orawa-Nowy Targ Basin and the southern slopes of the Gorce Mountains in the Polish sector of the Outer Carpathians. Geologically, the region is built of the Upper Cretaceous–Palaeogene turbiditic deposits representing sedimentary successions of the Krynica Subunit of the Magura Nappe and the Neogene–Quaternary fresh-water deposits filling the Orawa-Nowy Targ Basin. The Magura Nappe in the described area is represented by the thick-bedded sandstones of the Magura Formation and thin-and medium-bedded sandstone-shale deposits of the Malcov Formation, which are well-exposed in numerous outcrops, especially in the Łopuszna stream valley. The Magura Nappe deposits were folded and cut by a fault system in the Miocene. The presented area displays varied geomorphological relief and picturesque landscapes. Moreover, rare species of fauna and flora occurring here, as well as the still-alive culture of the Podhale Highlanders and continuously improving tourist infrastructure additionally contribute to the development of geotourism in this area. In addition, this area is an increasingly popular place among cyclists, thanks to the development of a network of bicycle paths, therefore the proposed geotourist bicycle path will extend the offer for this group of tourists.